Infusions and decoctions of Castanea sativa flowers as effective antitumor and antimicrobial matrices - Carocho, Márcio (2014)
Chestnut trees are one of the most important crops in the north-eastern part of Portugal, representing millions of euros of yearly income. There are many ancestral claims of the health benefits of the consumption of chestnut flowers in infusions that remain unproven. In this manuscript, the antitumor and antimicrobial potential of chestnut flowers from two cultivars, Judia and Longal, extracted through infusions and decoctions are reported. In terms of antitumor activity, the most sensitive cell lines were HepG2 and HCT15 with the cultivar Judia showing higher activity for HCT15 and Longal for HepG2, regardless of the extraction methods. Regarding the antibacterial activity of the extracts, decoctions proved to be more effective with lower minimum inhibition concentrations, while infusions were better in terms of antifungal activity. The good overall antimicrobial activity could justify the inclusion of the flowers in food chain processing to act as a natural antimicrobial. Furthermore, the results corroborate some of the ancestral claims of the consumption of these flowers. (C) 2014 Elsevier B.V. All rights reserved.